Pemberdayaan Anak Dengan Sosialisasi Dampak Penggunaan Gadget Dalam Rangka Memperingati Hari Anak - Pelu, Musa; Firdiyanti, Errysa Ayu; Prasetyowati, Rachma Intan; Safera, Tessa Bela (Society : Jurnal Pengabdian Masyarakat, 2023)
This study discusses the impact of Gadget use on students at SDN Joho 02. Gadgets have become a commonly use d communication tool in various circles, including children. Gadgets have positive benefits by increasing children's knowledge and creativity, but can also have negative effects if used excessively. Gadget addiction can lead to poor academic performance, lack of enthusiasm for learning, and lack of time discipline.This research uses a descriptive method combined with lecture, discussion, and question-and-answer methods. The media used to socialize the impact of using Gadgets is posters. The results showed that many students are addicted to Gadgets, which reduces their chances of success. Socialization of the impact of Gadget use was carried out by understanding the dangers of excessive Gadget use, as well as giving challenges to participants to reduce Gadget use for one week. Based on the results of the socialization conducted by the KKN UNS team, it can be concluded that the socialization of the impact of Gadget use on elementary school students went smoothly and according to plan. Elementary students gained positive knowledge and experience in managing the use of Gadgets. This activity will help students use Gadgets more wisely.Â